Cav1.4 congenital stationary night blindness is associated with an increased rate of proteasomal degradation - Sadeh, Tal T.; Baines, Richard A.; Black, Graeme C.; Manson, Forbes (Frontiers in Cell and Developmental Biology, 2023)
Pathogenic, generally loss of function, variants in CACNA1F, encoding the Cav1.4α1 calcium channel, underlie congenital stationary night blindness type 2 (CSNB2), a rare inherited retinal disorder associated with visual disability. To establish the underlying pathomechanism we investigated 10 clinically–derived CACNA1F missense variants located across pore-forming domains, connecting loops and the carboxy-tail domain of the Cav1.4 subunit. Homology modelling showed that all cause steric clashes; informatic analysis correctly predicted pathogenicity for 7/10 variants. In vitro analyses demonstrated that all variants cause a decrease in current, global expression and protein stability and act through a loss of function mechanism and suggest that the mutant Cav1.4 proteins were degraded by the proteasome. We show that the reduced current for these variants could be significantly increased through treatment with clinical proteasome inhibitors. In addition to facilitating clinical interpretation, these studies suggest that proteasomal inhibition represents an avenue of potential therapeutic intervention for CSNB2.